2015
DOI: 10.4067/s0034-98872015000200006
|View full text |Cite
|
Sign up to set email alerts
|

Tratamiento quirúrgico del hiperparatiroidismo asociado a insuficiencia renal crónica: Experience in 71 patients

Abstract: (Rev Med Chile 2015; 143: 190-196)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
1
0
3
Order By: Relevance
“…In most cases ultrasonography detects 2 or 3 parathyroid glands. Pulgar, following 71 patients (of which 58 with sHPT and 13 with tertiary hyperparathyroidism), describes pathological changes of parathyroids in 38 of the cases (53.5%) of which only in 9 cases the hyperplasia of all 4 parathyroids was present (15). Another study revealed by ultrasound only 139 hyperplastic parathyroids in 47 patients with sHTP -between 2 and 4 glands in each case (16).…”
Section: Imaging Of Parathyroid Glandsmentioning
confidence: 99%
“…In most cases ultrasonography detects 2 or 3 parathyroid glands. Pulgar, following 71 patients (of which 58 with sHPT and 13 with tertiary hyperparathyroidism), describes pathological changes of parathyroids in 38 of the cases (53.5%) of which only in 9 cases the hyperplasia of all 4 parathyroids was present (15). Another study revealed by ultrasound only 139 hyperplastic parathyroids in 47 patients with sHTP -between 2 and 4 glands in each case (16).…”
Section: Imaging Of Parathyroid Glandsmentioning
confidence: 99%
“…Si bien, en el estudio de Sanint (6) describen que se realizó autotrasplante, hubiera sido valioso conocer su localización, dado que diferentes estudios han documentado una buena correlación entre los hallazgos de los marcadores bioquímicos y el sitio de la toma de la muestras de laboratorio con respecto a los valores de PTH (4,8,9); por otro lado, resultaría interesante conocer el resultado de patología, debido a que se ha observado una alta asociación entre los hallazgos histopatológicos, el comportamiento clínico y la refractariedad al tratamiento.…”
Section: Hyperparathyroidism and Chronic Kidney Diseaseunclassified
“…HPTS o HPTT, siendo dos enfermedades que tienen una fisiopatología y un comportamiento clínico diferentes, se analizan e investigan de manera conjunta puesto que ambas se ven asociadas a la ERC y constituyen la minoría de los pacientes tratados con paratiroidectomía, en especial casos de HPTS; la presencia de hiperplasia o adenomas de las glándulas paratiroides tienen indicación quirúrgica y pueden estar presentes en pacientes con HPT secundario o terciario (4,8).…”
Section: Hyperparathyroidism and Chronic Kidney Diseaseunclassified
See 1 more Smart Citation